Metaphor and Effective Language Learning - Muh. Saeful Effendi (Universitas Negeri Padang, 2014)
The writer digests that learning foreign language is a hard effort without considering the mind participation. Text of Metaphor is something that fits right to the process of first language acquisition which makes use mind power and sometime emotionally involved. Metaphor is not only linguistic but also conceptual phenomenon. Word in language is valuable thing and dynamic which is culturally rich of meaning. When People say to their children about life “life is ocean”, it implies the work of mind, emotion, experience about culture and the sense of aesthetic.So, metaphor is something possible for any reason, particularly for learning foreign language. Metaphor can be a bridge to facilitate the abstract concept by the more concrete concept. Metaphor in literature is such embedded feature which makes sense every single word. In short, Metaphor cultivates language as the most valuable tools in conveying ideas. Moreover, understanding theory of metaphor is the fundamental aspect to lead understanding of language learning.In conclusion, metaphor in English language teaching gives opportunity for learners to optimize their strength. Metaphor is effective for learning language. Metaphor also makes learners focus on the form of language. Furthermore, metaphor helps learners to handle linguistic creativity